METODE RESITASI DALAM MENINGKATKAN ASPEK KOGNITIF, AFEKTIF DAN PSIKOMOTORIK SISWA - Shinta Maghfiroh Ning Tia; Khoirul Anwar; Nur Khamim (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Education plays a very important role in developing quality human resources. The level of religious knowledge at MTsN 5 Banyuwangi varies from one student to another, there are students who are very good at knowing, understanding, living, and having good morals in experiencing the teachings of Islam originating from the Al-Qur'an and Hadith. One of the methods applied to involve students actively, in order to improve learning outcomes is to use the recitation method. The individual recitation method is giving assignments individually. The purpose of this study was to determine the implementation of individual recitation methods in increasing students' knowledge, attitudes, and motor skills in fiqh subjects at MTsN 5 Banyuwangi. This research uses a qualitative descriptive approach. Data collection techniques in this study used interviews, observation, and documentation. Data analysis techniques in this thesis are done in several ways, namely data condensation, data presentation, and drawing conclusions. Test the validity of the data using source triangulation and technique triangulation. The results of this study are: 1) The individual recitation method can increase students' knowledge of fiqh subjects at MTsN 5 Banyuwangi. The knowledge in question is in the form of understanding, evaluating, discriminating, remembering, and applying. 2) The individual recitation method can improve students' attitudes towards fiqh subjects at MTsN 5 Banyuwangi. The attitude in question is responsibility, and independence. 3) The individual recitation method can improve students' motor skills in the Fiqh subject at MTsN 5 Banyuwangi. The skills in question are imitation, emphasis, and naturalization